DAMPAK APLIKASI SHOPEE TERHADAP DINAMIKA PERMINTAAN DAN PENAWARAN: KAJIAN LITERATURE - Nurohman, Dwi Aris; Amina, Nurtyasih Wibawanti Ratna (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study explores the impact of the Shopee application on demand and supply dynamics. In the digital era, e-commerce platforms such as Shopee have a strategic role in shaping market trends. This study analyzes various literature to evaluate how the promotions and discounts that Shopee offers affect consumer behavior and seller strategies. The findings show that promotion is effective in increasing consumer buying interest. This triggers sellers to expand the variety and quantity of products they offer. In addition, the Shopee review system also plays an important role in influencing consumer purchase decisions. Sellers with positive reviews tend to get an increase in sales, which leads to an improvement in the overall quality of the product. This study confirms that Shopee not only acts as a mediator between sellers and buyers but also as an active regulator of market dynamics through their internal policies. By identifying and understanding this strategic impact, industry players can further optimize their marketing strategies within the e-commerce ecosystem. This means that Shopee helps create a dynamic market environment and facilitates the sustainable growth of the digital economy.